Case report: Overlap syndrome of neuromyelitis optica spectrum disorder with anti-Argonaute antibodies - Liu, Pei; Lin, Xuemei; Wu, Songdi (Frontiers in Immunology, 2024)
Aquaporin-4 antibodies (AQP4-Abs) are a diagnostic marker for patients with a demyelinating disease called neuromyelitis optica spectrum disorder (NMOSD). Anti-argonaute antibodies (AGO-Abs) present as potential biomarkers of the overlap syndrome between NMOSD and other autoimmune diseases. We present the case of an adult female with numbness, tingling, and burning sensations in her arms and subsequent bilateral internuclear ophthalmoplegia. Brain-cervical-thoracic magnetic resonance imaging (MRI) showed T2 hyperintensities in the dorsal brain stem and around the midbrain aqueduct and longitudinally transverse myelitis with homogeneous enhancement on gadolinium-enhanced MRI. The contemporaneous detection of AQP4-Abs and AGO1-Abs led to a definite diagnosis of overlap syndrome of NMOSD with AGO1-Abs. The patient was treated with immunosuppressive agents, including corticosteroids and immunoglobulins, and achieved remission. This case highlights a novel phenotype of the NMOSD with AGO1-Abs overlap syndrome, which presents with relapsing brainstem syndrome and longitudinally extensive myelitis with acute severe neurological involvement. The promising prognosis of the disease may serve as a distinct clinical profile. Broad screening for antibodies against central nervous system autoimmune antigens is recommended in suspected patients with limited or atypical clinical manifestations.